Emergency Motor Stopper Using Ultrasonic Sensor - SAHAK, AINA ZHAFIRAH; , LILYWATI BAKAR; ZURINA ABDUL WAHAB, (Progress in Engineering Application and Technology, 2025)
In order to improve motor safety and operational reliability, this project proposes the design and implementation of an emergency motor stopper that makes use of an ultrasonic sensor. Relays, LED indicators, an Arduino microprocessor, and an ultrasonic sensor are all integrated into the system to provide rapid motor control and real-time motion detection. In order to process detected distances, the ultrasonic sensor connects with the Arduino and continuously scans a 50 cm radius for impediments. A red LED glows to indicate an emergency stop, and the motor automatically stops after a 5-second lag when an obstruction is detected. The technology flashes a green LED and restarts the motor after the obstruction has been removed. In order to assess sensor accuracy and response time, the project technique comprised circuit design, Arduino coding, and iterative hardware testing. The findings show that the system effectively functions within the specified range and consistently stops the motor within 5 seconds after detecting an impediment, guaranteeing safety without completely shutting off the motor's power supply. By offering a user-friendly, automated, and flexible solution appropriate for a range of applications, including industrial machinery and safety systems, this creative design tackles the difficulties associated with dynamic motor safety. The results emphasise the value of automation in reducing accidents and improving maintenance procedures, as well as the necessity of using ultrasonic sensors for accurate obstacle identification. With major ramifications for both personal and industrial safety regulations, this technology offers a scalable and economical approach to vehicle safety.